2015
DOI: 10.2458/azu_rc.57.18118
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Small Graphitization Reactors for Ultra-Microscale 14C Analysis at the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) Facility

Abstract: ABSTRACT. In response to the increasing demand for 14 C analysis of samples containing less than 25 µg C, ultra-small graphitization reactors with an internal volume of ~0.8 mL were developed at NOSAMS. For samples containing 6 to 25 µg C, these reactors convert CO 2 to graphitic carbon in approximately 30 min. Although we continue to refine reaction conditions to improve yield, the reactors produce graphite targets that are successfully measured by AMS. Graphite targets produced with the ultra-small reactors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In the past decade, efforts have been made to lower the sample size for conventional graphite targets, for example by adjusting the graphitization reaction parameters, e.g. improving the pre-treatment and performance of the catalyst powder (Freeman et al 2016) or changing the reaction volume (Shah Walter et al 2016) or temperature (Santos et al 2007). As a result, the typical sample size for conventional graphite target analysis has dropped from above 10 mg to 3 mg of CaCO 3 for routine analysis in most AMS facilities, though samples as small as 1 mg CaCO 3 can be run (Freeman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, efforts have been made to lower the sample size for conventional graphite targets, for example by adjusting the graphitization reaction parameters, e.g. improving the pre-treatment and performance of the catalyst powder (Freeman et al 2016) or changing the reaction volume (Shah Walter et al 2016) or temperature (Santos et al 2007). As a result, the typical sample size for conventional graphite target analysis has dropped from above 10 mg to 3 mg of CaCO 3 for routine analysis in most AMS facilities, though samples as small as 1 mg CaCO 3 can be run (Freeman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…isotope dilution and "modern-dead" methods; Pearson et al, 1998;Santos et al, 2007;Fernandez et al, 2014;Shah Walter et al, 2015), the direct measurement method employed here is better-suited for the RPO instrument for the following reasons:…”
Section: Nosams Rpo Blank Correctionmentioning
confidence: 99%
“…For 2-and 5-toggle experiments, individual fractions were recombined within the vacuum line before transferring to a 6 mm Pyrex tube to keep subsequent steps identical across all experimental conditions. Each experiment was performed in duplicate and the CO 2 mass from each analysis was quantified separately before pairs were combined for ultra-small 14 C analysis (Shah Walter et al, 2015). Results are corrected for C ratio as measured on the AMS (Santos et al, 2007) and are reported in Fm notation following Stuiver and Polach (1977).…”
Section: Nosams Rpo Blank Correctionmentioning
confidence: 99%
“…Santos et al 2007;Delqué-Količ et al 2013), but only one of these studies has specifically targeted small carbonate samples for use in paleoceanograpic research (Shah Walter et al 2015).…”
Section: Introductionmentioning
confidence: 99%